2011
DOI: 10.1007/s00256-011-1227-y
|View full text |Cite
|
Sign up to set email alerts
|

Metaphyseal and diaphyseal chondroblastomas

Abstract: Pure metaphyseal and/or diaphyseal CB are exceedingly rare. A presumptive diagnosis may be considered in the appropriate age group in the presence of chondroid matrix, perilesional edema, periosteal reaction, and marginal sclerosis. Regardless of all the diagnostic possibilities, biopsy may still be required. However, knowledge of this entity will help make the final diagnosis and guide the correct treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…Although the tumor may secondarily involve the metaphysis and even the diaphysis (probably by extension across the physis), primary metaphyseal or diaphyseal occurrences of this disease without epiphyseal or apophyseal involvement are exceptionally rare 14 .…”
mentioning
confidence: 99%
“…Although the tumor may secondarily involve the metaphysis and even the diaphysis (probably by extension across the physis), primary metaphyseal or diaphyseal occurrences of this disease without epiphyseal or apophyseal involvement are exceptionally rare 14 .…”
mentioning
confidence: 99%
“…In contrast one study19 has been shown that non-epiphysial CBs were associated with a lower risk of recurrence. The reason may be related to this fact that non-epiphysial lesions are away from the epiphysis, so a more aggressive surgical approach can be taken.…”
Section: Discussionmentioning
confidence: 73%
“…Although one case in this latter tabulation is listed as being diaphyseal, this is in error, as the report by Dahlin and Ivins [1] that is referenced did not contain any examples of diaphyseal CB. In their report, however, Maheshwari et al provide a separate listing of 51 cases of extra-epiphyseal CBs in small, tubular, and flat bones that had been reported from 1951 to 2009, 6 of which were purely diaphyseal [15].…”
Section: Discussionmentioning
confidence: 94%
“…The remainders were described as Bcortical,â nd one as a Bsurface^lesion, but no details of these cases are given [6]. All of the metaphyseal-and diaphyseal-based CBs described by Maheshwari et al were also intramedullary [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation